Sustainable Value-Based Online Marketing Communication Strategy: Namira Ecoprint Case Study - Nugroho, Gregorius Aditya Prasetyo; Nasution, Arman Hakim (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This research aims to develop an online marketing communication strategy for namira ecoprint, an ecoprint SME facing challenges in conveying its brand online. It investigates the impact of marketing strategies on sustainable value creation in the ecoprint industry. Using a mixed-methods approach, the study combines qualitative data from literature, interviews, and observations with quantitative data from an online survey. The resulting strategy is evaluated using SEM-PLS analysis within the framework of alternative marketing strategies adapted for the ecoprint industry's channel ecosystem. The findings indicate that the proposed strategy effectively enhances Namira Ecoprint's brand image as environmentally friendly and provides a foundation for implementing marketing tactics in collaboration with the creative industry.